PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP VOLUME BALOK SISWA KELAS V SDN GUNUNG 01 MELALUI MODEL PBL BERBANTUAN PAPAN SEGITIGA AJAIB - Pristiani, Dwi Arini; Soebagyo, Joko (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
Abstract. This study aims to test the use of the PBL (Problem Based Learning) learning model assisted by a magic triangle board in improving the ability to understand the concept of cuboid volume of grade V students of SDN Gunung 0l. The research method used is an experiment with a one-group pretest-posttest design. Data on students’ conceptual understanding of calculating cuboid volume were collected through pretest and posttest, after the implementation of the PBL (Problem Based Learning) model assisted by a magic triangle board. Data analysis using the Wilcoxon hypothesis test. The results of the analysis showed a significance value of 0.000, which is smaller than 0.05 (p <0.05), so the null hypothesis (H₀) is rejected. This indicates that there is a significant increase in students’ understanding of the concept of cuboid volume after the implementation of the PBL (Problem Based Learning) learning model assisted by a magic triangle board. Thus, this study concludes that the PBL (Problem Based Learning) learning model assisted by the magic triangle board is effective in improving the ability to understand the concept of cuboid volume in grade V students of SDN Gunung 01.